A top-down design for easy gram scale synthesis of melem nano rectangular prisms with improved surface area. Issue 61 (3rd December 2021) - Nikookar, Mahsa; Rezaeifard, Abdolreza; Maasoumeh Jafarpour; Grzhegorzhevskii, Kirill V.; Ostroushko, Alexander A.
Abstract : A novel practical method for the gram scale preparation of melem possessing a nano rectangular prism morphology and improved specific surface area through a top-down depolymerization design was developed. Abstract : An unprecedented top-down design for the preparation of melem by 1 h stirring of melamine-based g-C3 N4 in 80 °C concentrated sulfuric acid (95–98%) was discovered. The melem product was formed selectively as a monomer on the gram scale without the need for controlled conditions, inert atmosphere, and a special purification technique. The as-prepared air-stable melem showed a distinctive nano rectangular prism morphology that possesses a larger surface area than the melems achieved by traditional bottom-up designs making it a promising candidate for catalysis and adsorption processes.